(untitled) (Academia Journal of Medicine, 2023)
ChatGPT, an AI chatbot, has the potential to revolutionize the field of orthodontics by providing valuable support to orthodontists, staff, and patients. By leveraging its natural language processing capabilities, ChatGPT can assist in several ways, including answering patient questions, providing educational information about orthodontic treatments, offering post-treatment guidance, and even supporting staff in managing administrative tasks. The implementation of ChatGPT in orthodontic practices can improve patient satisfaction, streamline communication, and ultimately enhance the overall orthodontic experience for both patients and practitioners. This abstract provides an overview of the role of ChatGPT in orthodontics and highlights its potential impact on the field.